2017
DOI: 10.3390/w9040276
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of IMERG Level-3 and TMPA 3B42V7 in Estimating Typhoon-Related Heavy Rain

Abstract: Typhoon-related heavy rain has unique structures in both time and space, and use of satellite-retrieved products to delineate the structure of heavy rain is especially meaningful for early warning systems and disaster management. This study compares two newly-released satellite products from the Integrated Multi-satellitE Retrievals for Global Precipitation Measurement (IMERG final run) and the Tropical Rainfall Measuring Mission (TRMM) Multi-satellite Precipitation Analysis (TMPA 3B42V7) with daily rainfall o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…IMERG is a calibrated, multi-sensor retrieval that provides 30-minute, 0.1 • ×0.1 • , estimates of precipitation. The performance of IMERG for east Asia is known to be good in comparison to surface rainfall measurements: Ning et al (2016) reported 15 biases of less than 0.1 mm/day in daily-mean rainfall over 20-month comparison, and showed that IMERG captured both the amount and occurrence frequency of heavy rainfall during that period; Wang et al (2017) investigated cases of extreme rain and showed that IMERG is accurate to within 10 percent over the 20-60 mm/h range.…”
Section: Gpmmentioning
confidence: 99%
“…IMERG is a calibrated, multi-sensor retrieval that provides 30-minute, 0.1 • ×0.1 • , estimates of precipitation. The performance of IMERG for east Asia is known to be good in comparison to surface rainfall measurements: Ning et al (2016) reported 15 biases of less than 0.1 mm/day in daily-mean rainfall over 20-month comparison, and showed that IMERG captured both the amount and occurrence frequency of heavy rainfall during that period; Wang et al (2017) investigated cases of extreme rain and showed that IMERG is accurate to within 10 percent over the 20-60 mm/h range.…”
Section: Gpmmentioning
confidence: 99%
“…Because it includes rain‐gauge measurements, we expect IMERG to perform well (on average) over data‐rich regions, but uncertainties for individual cases may nevertheless be large. The reliability of IMERG for individual cases of extreme rainfall during the east Asian summer monsoon was investigated by Wang et al (), who evaluated IMERG for eight typhoons over the coastal China. They found relative biases of the order of 10% for rain rates in the range 20–60 mm/day; above/below this range, IMERG underestimated/overestimated rainfall rates by approximately ±20%.…”
Section: Description Of the Model Evaluation Framework And Scmrex Casmentioning
confidence: 99%
“…With recent huge advancements in remote sensing techniques and satellite‐based retrieval algorithms (Joyce et al, ), a series of satellite precipitation products with different spatial and temporal resolutions have been developed under several scientific missions and centers, for example, Tropical Rainfall Measurement Mission (TRMM) (Huffman et al, ; Huffman et al, ), Climate Precipitation Center morphing method (Joyce et al, ), and the Integrated Multisatellite Retrievals for Global Precipitation Measurement (IMERG) (Huffman et al, ). Generally, TRMM 3B42 and 3B43 data sets demonstrated high accuracies and qualities in the TRMM era from 1998 to 2014 (Ma et al, ; Wang et al, ), and based on the latest correction algorithm, the TRMM Multisatellite Precipitation Analysis (TMPA) data has been updated to those of the V7 with lesser random error than the V6 version (Ming‐zhe et al, ). However, the TRMM satellite reentered Earth's atmosphere on 17 June 2015 after more than 17 years in service.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, IMERG performed reasonably well at daily and seasonal time scales over the Mexican region (Mayor et al, ). And compared with TRMM TMPA V7 data, IMERG (Level 3 product) also performed better in detecting rainfall events, especially for slight rainfall, over the entire Mekong River Basin at daily scale (Wang et al, ). Additionally, the IMERG demonstrated more enormous potentials for detecting snow and ice crystals, as well as the detection of slight rainfall than those of the 3‐hourly TRMM 3B42 V7 in the warm season, 2014, over the Tibetan Plateau, China (Ma et al, ; Huffman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation